EFFECTIVE MANAGEMENT OF BUSINESS REPUTATION AS A RELEVANT WAY TO NAVIGATE RUSSIAN COMPANIES FROM THE STANDARDS OF CORPORATE GOVERNANCE TO THE PRINCIPLES OF CORPORATE GOVERNANCE - Oleg Igorevich Kalinskiy (Вестник Северо-Кавказского федерального университета, 2022)
The process of transition from corporate governance to corporate behavior in Russia via the effective management of the enterprise reputation is analyzed. Main methods for evaluating enterprise’s corporate reputation are analyzed and aggregated.